The Socio-Legal Study of Rights Fulfillment and Fostering Prisoner at Correctional Institutions in Covid 19 Pandemic - Nur Rochaeti; Irma Cahyaningtyas (Jurnal Dinamika Hukum, 2021)
As part of the integrated criminal justice system, Correctional Institutions play a role as law enforcement officers in addition to having a strategic role in the formation of Human Resources (HR) that are independent, responsible, quality, and dignified. The correctional system is a more humane and normative treatment system for inmates based on Pancasila and is characterized by rehabilitative, corrective, educative, and integrative or order regarding the direction and boundaries as well as ways of fostering prisoner based on Pancasila, which are carried out in an integrated manner between the coach as  a correctional officer , being fostered, and integrative or order regarding the direction and boundaries as well as the way of fostering the prisoners based on Pancasila which are carried out in an integrated manner between the coach, prisoners and integrative Public. The problem is how is the socio-legal study of fulfilling prisoner’s rights and fostering in correctional institutions during the COVID 19 pandemic. The research method used is socio-legal, to analyze the policy on Act Number 12 of 1995 of correctional and fulfillment of prisoner’s rights in coaching during the COVID 19 pandemic. The results of the study analysis that the policy in Act Number 12 of 1995 of correctional currently does not accommodate the fulfillment of prisoner’s rights in correctional facilities, prisoner’s guidance is carried out by providing useful skills after leaving correctional facilities for independence and personality, which cannot be fully utilized. Inmates optimally, after leaving penitentiary, infrastructure facilities, as well as health workers in correctional, are needed, especially when the COVID 19 pandemic. The release of prisoners is a dilemma in the condition of the COVID 19 pandemic.Keywords: arranged socio-legal; fostering prisoner; correctional institutions; COVID 19